Caracterização da fertilidade do solo, distribuição do sistema radicular e índice de qualidade do solo no Ecossistema Restinga do Litoral Paulista - Bonilha, Rodolfo Martins (2011)
The Restinga forest is a set of plant communities in mosaic, determined by the characteristics of their substrates as a result of depositional processes and ages. And of all the ecosystems associated with the Atlantic, the most fragile and susceptible to human disturbance. In this complex mosaic are the physiognomies of restinga forests of high-stage regeneration (high restinga) and middle stage of regeneration (low restinga), each with its plant characteristics that differentiate them. Located on the coastal plains of the Brazilian coast, suffering internal influences both the continental slopes, as well as navy. His solo comes from the Quaternary and are subject to constant deposition of sediments. The climate on the coast, according to Köppen classification, type is tropical. In recent decades, with growing concern about natural resources and environmental quality, intensified research, resulting in the definition of soil quality (SQ), strongly rooted in the concept of sustainability. To this end, several models have been proposed in an attempt to assess soil quality index (SQI). The monitoring of soil quality should be directed to detect trends that are measurable changes in a period of time. The objectives of this study were: a) Comparative evaluation of the characterization of soil fertility, through chemical and physical parameters under restinga forest of high and low, with respect to distribution of the root in the soil profile, and b) Determine the index Soil Quality for restinga forest in high-and middle-stage regeneration and a resting area with no vegetation. This work was conducted in four locations: (1) Anchieta Island, Ubatuba, (2) Juréia-Itatins Ecological Station, Iguape, (3) Vila das Pedrinhas, Comprida Island; and (4) Cardoso Island, Cananeia. Studies on soil fertility have been made in depths of 0 to 5, 00-10, 00-20, 20-40 and 40 to 60cm for the chemical and physical analysis, with five replicates for each vegetation type, for each study site, each composed of twelve subsamples. Also being evaluated the distribution of the root in the soil profile. To determine the rate of soil quality, chemical analysis were made, microbiological and physical-layer 0-10cm depth. Using two models in determining the rate of soil quality: Additive Model (MA) and Comparative Additive Model (MAC). It is concluded that the root system for all studied vegetation types found in the more superficial layers, 0-10 and 10-20cm, mainly in the 0-10cm (80%), that low levels of calcium and elevated aluminum restrict root development. All the studied have low soil fertility, with base saturation values below 16%, where most of these environments CEC is occupied by aluminum. The additive model produces quantitative results and the additive model comparative quantitative and qualitative results (ground potential), the SQI values were obtained by the MAC for all local and low vegetation types and realistic, demonstrating the low potential for biomass production in these soils, and its low resilience. Values similar to the forests with and without vegetation showed numerically the consideration that the restinga is an edaphic vegetation. And that the use of routine chemical analysis is sufficient to determine the IQS.